Efeito da eletroacupuntura na dor, aspectos somatossensorias, funcionais e psicoemocionais de pacientes com lombalgia crônica inespecífica - Leite, Paula Michele dos Santos (2020)
Introduction: Chronic nonspecific low back pain (CNSLBP) is a common affection condition and corresponds to one of the most disabling conditions in the world. The search for non-drug therapies is growing, among them, electroacupuncture (EA). However, to date, there are no studies that analyze the effect of EA alone on CNSLBP. Objectives: To analyze the effect of electroacupuncture on pain, somatosensory, functional and psycho-emotional aspects of patients with nonspecific chronic low back pain. Method: This is a randomized, double-blind controlled clinical trial. Patients were randomly allocated to one of the four study groups. There was a treatment group (EA) and three control groups. In Control Group 1 (CTR 1), the electrical stimulus lasted only 45 seconds. In Control Group 2 (CTR 2), the electroacupuncture device was turned off, but the needles were kept inserted. In Control Group 3 (CTR 3), the needles were immediately removed after puncture. The treatment was performed three times a week, in a total of ten sessions. Resting and moviment pain intensity were investigated using the 11-point pain numerical scale. To characterize pain, McGill's pain questionnaire was used. Somatosensory aspects were analyzed by measuring tactile detection threshold (esthesiometry), pressure pain threshold (algometry), temporal summation test and conditioned pain modulation test. To analyze functional aspects, the impact of pain on functionality (Oswestry questionnaire) and functional disability (Roland-Morris disability questionnaire) were investigated. The psycho-emotional aspects were observed through pain catastrophizing (pain catastrophizing questionnaire) and kinesiophobia (Tampa kinesiophobia questionnaire). Quality of life was analyzed using the Euroqol-5D questionnaire. Results: A total of sixty-nine patients participated in the study. No significant differences were found in pain intensity or quantitative sensory test responses when comparing the electroacupuncture group to the three control groups. There was a significant reduction in both resting and moving pain intensity in the EA, CTR 1, and CTR 3 groups. The impact of pain on functionality, functional disability, and pain catastrophizing were significantly lower after the ten electroacupuncture sessions in the patients with nonspecific chronic low back pain in the present study. Kinesiophobia and quality of life showed no significant changes after the sessions in either group. Conclusions: Electroacupuncture alone reduces pain intensity, improves functional aspects and decreases pain catastrophizing in patients with chronic non-specific low back pain. However, EA was not effective regarding central sensitization, kinesiophobia or the quality of life of these patients.